Synergy Between Tarbiyah Awaliyah and Madrasah: A Collaborative Model for Shaping Children's Character in the Era of Information Disruption - Sherlin Nabila; Candra Kirana; Ajeng Novianti; Mega Wulandari; Ajeng Lutfianti; Iwhan Wahyudi; Muhammad Idris (Sustainable, 2023)
The era of information disruption presents unprecedented challenges to children’s moral and cognitive development, necessitating robust educational interventions. This study explores the urgent need for synergy between Tarbiyah Awaliyah (early Islamic education) and formal Madrasah to foster resilient character in children. Employing a qualitative literature review methodology, this research synthesizes peer-reviewed articles from Google Scholar published between 2018 and 2023. The findings reveal that current educational practices often operate in isolation, creating pedagogical discontinuity and value inconsistency that leave children vulnerable to digital threats. To address this, a collaborative synergy model is proposed, comprising six interdependent components: aligned curriculum frameworks, professional learning communities, integrated assessment systems, family partnerships, progressive digital literacy pathways, and community resource networks. This model establishes a cohesive moral ecosystem that transitions children from foundational value internalization to advanced critical digital discernment grounded in Islamic ethics. Ultimately, this study provides actionable insights for educators and policymakers, emphasizing that sustainable character education in the digital age requires coordinated, multi-stakeholder engagement rather than isolated institutional efforts.